Revealing molecular and cellular heterogeneity in hypopharyngeal carcinogenesis through single-cell RNA and TCR/BCR sequencing - Tie, Cheng-Wei; Zhu, Ji-Qing; Yu, Zhan; Dou, Li-Zhou; Wang, Mei-Ling; Wang, Gui-Qi; Ni, Xiao-Guang (Frontiers in Immunology, 2024)
Hypopharyngeal squamous cell carcinoma (HSCC) is one of the malignant tumors with the worst prognosis in head and neck. The transformation from normal tissue through low-grade and high-grade intraepithelial neoplasia to cancerous tissue in HSCC is typically viewed as a progressive pathological sequence. Nonetheless, the alterations in diverse cell clusters within the tissue microenvironment (TME) throughout this progression and their impact on the development of HSCC are yet to be fully understood. We employed single-cell RNA sequencing and TCR/BCR sequencing to sequence 60,854 cells from nine tissue samples representing different stages during the progression of HSCC. This allowed us to construct dynamic transcriptomic maps of cells in diverse TME across various disease stages. We delineated the heterogeneity among tumor cells, immune cells (including T-cells, natural killer cells, B-cells, and myeloid cells), and stromal cells (such as fibroblasts and endothelial cells) throughout the disease's progression. We uncovered the alterations in function and state of distinct cell clusters in different stages of HSCC and identified specific clusters closely associated with its progression. Consequently, we discovered molecules like MAGEA3 and MMP3, pivotal for the diagnosis and treatment of HSCC. Our research sheds light on the dynamic alterations within the TME during the development of HSCC, which will help to understand its mechanism of canceration, identify early diagnostic markers, and discover new therapeutic targets.